(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the concept of religious tolerance and its crucial role in maintaining peace, social harmony, and interethnic unity, particularly in Uzbekistan. It emphasizes the importance of religious freedom, the guarantee of equal rights for all citizens, and the historical and contemporary practices of tolerance in the country. The principles of tolerance in Islam, historical examples, and the ongoing efforts by the Uzbek government to foster interethnic harmony are examined. The paper also highlights the role of international initiatives, such as the UN’s "Enlightenment and Religious Tolerance" resolution, in promoting global peace. The article demonstrates how religious and ethnic diversity in Uzbekistan has been a cornerstone of national stability and development, contributing to a peaceful and prosperous society.